(untitled) (Annals of Medical Research, 2021)
Aim: In adults, functional constipation (FC) is more common in individuals with overactive bladder (OAB) than in those without OAB. In this study, we evaluated the effects of the constipation treatment on OAB symptoms in women who have OAB and FC. Material and Methods: : A total of 417 patients, diagnosed with OAB and FC in our clinic between June 2016 and June 2019, were prospectively evaluated. After applying the exclusion criteria, 54 female volunteers between 50-79 years of age were enrolled in the study. FC treatment of the individuals, who were first examined in the Urology clinic, were accomplished under supervision of a gastroenterologist. Internationally validated questionnaires Rome IV and OAB-V8 were used in diagnosis and follow-up of FC and OAB, respectively.Results: The mean OAB-V8 scores before and after the treatment of constipation were 25.21±6.16 and 14.81±5.93, respectively. Among all questions, statistically significant decrease was observed especially 1st, 3rd, and 6th questions (frequency, urgency, nocturia). After FC treatment alone, the total OAB-V8 score decreased below the level of the sensitivity and specificity cut-off value for the diagnosis of OAB in 13 patients (24%).Conclusion: OAB and FC are common clinical problems in the middle-aged and elderly women. In these patients, FC treatment before OAB medication may reduce frequency, urgency and nocturia symptoms of OAB significantly.